The Urgency of Biology Teaching Materials Based on Islamic Values - Adi Hartono; Fitri Febrianti Ginting; Rizki Bob Anggara; Mahfuza Delila Harahap; Rizka Ramadani Dalimunthe; Rega Armanda Rastanutra Sembiring Milala (International Journal on Advanced Science, Education, and Religion, 2024)
This qualitative research aims to find out how important Biology TeachingMaterials are based on Islamic values in senior high schools (SMA / MA). That isin Teladan High School, MAN 3 Medan, and MAN Sibolga. The purpose of thisdescriptive research is to make a description, description systematically, factuallyand accurately about the facts, characteristics and relationships between thephenomena investigated.Data collection techniques in qualitative research are byconducting surveys.Integration of the Koran and Hadith in biology learning needsto be done to foster Islamic values in students in order to achieve the objectives.